2016
DOI: 10.1287/orsc.2015.1039
|View full text |Cite
|
Sign up to set email alerts
|

Scrutiny, Norms, and Selective Disclosure: A Global Study of Greenwashing

Abstract: U nder increased pressure to report environmental impacts, some firms selectively disclose relatively benign impacts, creating an impression of transparency while masking their true performance. We theorize circumstances under which firms are less likely to engage in such selective disclosure, focusing on organizational and institutional factors that intensify scrutiny and expectations of transparency and that foster civil society mobilization. We test our hypotheses using a novel panel data set of 4,750 publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
471
1
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 654 publications
(573 citation statements)
references
References 93 publications
(89 reference statements)
13
471
1
7
Order By: Relevance
“…In such contexts, maintaining legitimacy with key stakeholders might involve intentional deviation other than isomorphism with the global standards (Oliver, 1991). In showing that the externally legitimate practice was re-theorized to better serve the interests of key stakeholders, we join other recent efforts to develop new mechanisms by which corporations uniquely adopt global practices in an emerging economy where state influence is more salient (Marquis, Toffel, & Zhou, 2016;Okhmatovskiy & David, 2012).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In such contexts, maintaining legitimacy with key stakeholders might involve intentional deviation other than isomorphism with the global standards (Oliver, 1991). In showing that the externally legitimate practice was re-theorized to better serve the interests of key stakeholders, we join other recent efforts to develop new mechanisms by which corporations uniquely adopt global practices in an emerging economy where state influence is more salient (Marquis, Toffel, & Zhou, 2016;Okhmatovskiy & David, 2012).…”
Section: Discussionmentioning
confidence: 94%
“…Traditional perspectives on the global spread of CSR focus on the influence of international civil society organizations (Etzion & Ferraro, 2010;Marquis, Toffel, & Zhou, 2016), and research has shown a that a growing number of Chinese firms are subject to globalization pressures (Wang, 2009;Zhu, Cordiero, & Sarkis, 2012). Yet, also salient to these actors are multiple domestic stakeholders such as central and local governments (Hofman, Moon, & Wu, 2015;Liang, Ren, & Sun, 2015).…”
Section: Marquis Et Almentioning
confidence: 99%
“…The procedural and managerial value of social reporting is indirectly confirmed by the low number of schools (about 17% of the respondents) who consider social report as a marketing tool to increase the number of students enrolled. This looks positive if we consider the criticism addressed to social reporting, often considered as a mere greenwashing tool (Laufer, 2003;Marquis & Toffel, 2013).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Alternatively, they could express concern about superintelligence to portray themselves as responsible actors and likewise avoid regulation. This would be analogous to the strategy of "greenwashing" employed by companies seeking to bolster their reputation for environmental stewardship [78]. Indeed, there have already been some expressions of concern about superintelligence by AI technologists, and likewise some suspicion that the stated concern has this sort of ulterior motive [79].…”
Section: Prospects For Politicized Superintelligence Skepticismmentioning
confidence: 99%